2016
DOI: 10.5430/jnep.v7n5p27
|View full text |Cite
|
Sign up to set email alerts
|

Time on Task: Perceived and measured time in online courses for students and faculty

Abstract: Objective: A cross sectional, online survey study examined active course time and activity for students and faculty in online courses compared to their perceptions of time. Methods: Student self-reports of their estimated course time and percentage of time on individual tasks, and faculty estimates of student time as well as their own course activity time were obtained. This was compared to actual individual and course summary activity data as recorded by the learning platform (Blackboard). Descriptive and t t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…[22] Another study showed that both students and teachers agreed that learning activities in online courses must take a certain time, and that students found online courses more conducive to learning than physical classes, especially for discussion of topics. [23] During the epidemic, online teaching was conducted in some elementary schools and high schools in India, and significant differences in learning outcomes were found between students with different goals and perceptions of learning. The learning outcomes also relate to school types, locations, and genders of students.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Another study showed that both students and teachers agreed that learning activities in online courses must take a certain time, and that students found online courses more conducive to learning than physical classes, especially for discussion of topics. [23] During the epidemic, online teaching was conducted in some elementary schools and high schools in India, and significant differences in learning outcomes were found between students with different goals and perceptions of learning. The learning outcomes also relate to school types, locations, and genders of students.…”
Section: Introductionmentioning
confidence: 99%